2005
DOI: 10.1002/ijc.21492
|View full text |Cite
|
Sign up to set email alerts
|

Her‐2/neu and EGFR tyrosine kinase activation predict the efficacy of trastuzumab‐based therapy in patients with metastatic breast cancer

Abstract: Her-2/neu overexpression in human breast cancer leads to an aggressive biological behavior and poor prognosis. Although the anti-Her-2/neu antibody trastuzumab (Herceptin 1 ) has become a valuable therapeutic option for patients with Her-2/neu-overexpressing breast cancer, many patients do not benefit from this therapy. To evaluate the effect of receptor activation on tumor response, we have investigated the phosphorylation status of Her-2/neu and EGFR in 46 Her-2/neu-overexpressing tumor samples from trastuzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
5
32
3
Order By: Relevance
“…However, basal cell lines were more frequently resistant. In a previous study, a trend towards increased response was seen for patients with ERBB2-phosphorylated tumors (Hudelist et al, 2006). We observed a similar trend in a preliminary survey of trastuzumab-treated Figure 3 Western blot analysis of ERBB2 phosphorylation in serum-starved breast cancer cell lines.…”
Section: Further Considerationssupporting
confidence: 81%
See 1 more Smart Citation
“…However, basal cell lines were more frequently resistant. In a previous study, a trend towards increased response was seen for patients with ERBB2-phosphorylated tumors (Hudelist et al, 2006). We observed a similar trend in a preliminary survey of trastuzumab-treated Figure 3 Western blot analysis of ERBB2 phosphorylation in serum-starved breast cancer cell lines.…”
Section: Further Considerationssupporting
confidence: 81%
“…Even in conditions of monotherapy, the results may be difficult to interpret, as judged by our study of BCL. In the same previous report, the determination of the phosphorylation status of both ERBB2 and epidermal growth factor-receptor (EGFR) helped predict the response (Hudelist et al, 2006). Another study showed the efficiency of lapatinib (GW572016), a dual inhibitor of EGFR and ERBB2, to inhibit ERBB2 kinase in expressing cells was correlated with the level of ERBB2 expression and with the level of phosphorylated ERBB2 inhibition (Konecny et al, 2006).…”
Section: Further Considerationsmentioning
confidence: 91%
“…Although CIR-PBL showed higher rate of tumor inhibition than Herceptin in our study, more aggressive treatment with Herceptin including frequent infusion and the use of higher dose can result in better clinical outcome than infusion of CIR-PBL, as used by other groups. [23][24][25][26] Several reports have contributed to elucidate mechanism of Herceptin including interference receptor dimerization, blockade of phosphorylation of ErbB2 and ErbB3, inhibition of mitogen-activated protein kinase activity, and suppression of phosphatidylinositol 3 0 -kinase, and Akt. 38,39 In addition, it was proposed that Herceptin generates antibody-dependent cell-mediated cytotoxicity effect involving host NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Many methods have been used to therapeutically target Her-2-overexpressing cancers, including the use of anti-Her-2/neu antibodies. [23][24][25][26] Trastuzumab also known as Herceptin for humanized form, was found to inhibit the proliferation of human cancer cells that overexpress Her-2/neu, both in vitro and in vivo. 27,28 However, the clinical benefit is limited because its resistance to Herceptin therapy among Her-2/neu-overexpressing cancer cells arises in less than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fidelity of initial PP levels may be lost if tissues are not placed in appropriate fixatives within several minutes of removal from patients, unless preliminary studies are performed to document preservation of targets in prevailing procurement conditions. These changes in PP level, due to non-uniform tissue handling, may account for negative studies or the relatively weak associations between PP levels and outcomes that have been reported (Cunningham et al 2005;Hudelist et al 2006;Mitsiades et al 2007;Andre et al 2008).…”
Section: Discussionmentioning
confidence: 99%